HDAC inhibitors Panobinostat and Romidepsin enhance tax transcription in HTLV-1-infected cell lines and freshly isolated patients' T-cells - Schnell, Annika; Kohrt, Stephan; Aristodemou, Aris; Taylor, Graham P.; Bangham, Charles R. M.; Thoma-Kreß, Andrea (Frontiers in Immunology, 2022)
The viral transactivator Tax plays a key role in HTLV-1 reactivation and de novo infection. Previous approaches focused on the histone deacetylase inhibitor (HDACi) Valproate as a latency-reversing agent to boost Tax expression and expose infected cells to the host's immune response. However, following treatment with Valproate proviral load decreases in patients with HAM/TSP were only transient. Here, we hypothesize that other compounds, including more potent and selective HDACi, might prove superior to Valproate in manipulating Tax expression. Thus, a panel of HDACi (Vorinostat/SAHA/Zolinza, Panobinostat/LBH589/Farydak, Belinostat/PXD101/Beleodaq, Valproate, Entinostat/MS-275, Romidepsin/FK228/Istodax, and MC1568) was selected and tested for toxicity and potency in enhancing Tax expression. The impact of the compounds was evaluated in different model systems, including transiently transfected T-cells, chronically HTLV-1-infected T-cell lines, and freshly isolated PBMCs from HTLV-1 carriers ex vivo. We identified the pan-HDACi Panobinostat and class I HDACi Romidepsin as particularly potent agents at raising Tax expression. qRT-PCR analysis revealed that these inhibitors considerably boost tax and Tax-target gene transcription. However, despite this significant increase in tax transcription and histone acetylation, protein levels of Tax were only moderately enhanced. In conclusion, these data demonstrate the ability of Panobinostat and Romidepsin to manipulate Tax expression and provide a foundation for further research into eliminating latently infected cells. These findings also contribute to a better understanding of conditions limiting transcription and translation of viral gene products.
CRIS-Team WoS Importer:2022-09-16

Latency reversing agents: Kick and kill of htlv-1? - Schnell, Annika; Kohrt, Stephan; Thoma-Kreß, Andrea (International Journal of Molecular Sciences, 2021)
Human T-cell leukemia virus type 1 (HTLV-1), the cause of adult T-cell leukemia/lym-phoma (ATLL), is a retrovirus, which integrates into the host genome and persistently infects CD4+ T-cells. Virus propagation is stimulated by (1) clonal expansion of infected cells and (2) de novo infection. Viral gene expression is induced by the transactivator protein Tax, which recruits host factors like positive transcription elongation factor b (P-TEFb) to the viral promoter. Since HTLV-1 gene expression is repressed in vivo by viral, cellular, and epigenetic mechanisms in late phases of infection, HTLV-1 avoids an efficient CD8+ cytotoxic T-cell (CTL) response directed against the im-munodominant viral Tax antigen. Hence, therapeutic strategies using latency reversing agents (LRAs) sought to transiently activate viral gene expression and antigen presentation of Tax to enhance CTL responses towards HTLV-1, and thus, to expose the latent HTLV-1 reservoir to immune destruction. Here, we review strategies that aimed at enhancing Tax expression and Tax-specific CTL responses to interfere with HTLV-1 latency. Further, we provide an overview of LRAs including (1) histone deacetylase inhibitors (HDACi) and (2) activators of P-TEFb, that have mainly been studied in context of human immunodeficiency virus (HIV), but which may also be powerful in the context of HTLV-1.
CRIS-Team Scopus Importer:2021-06-04
Keywords: ATLL; HDAC-inhibitor (HDACi); HIV; HTLV-1; Kick and kill; Latency; Latency reversing agents (LRA); P-TEFb; Shock and kill; Tax

No antibiotics for asymptomatic bacteriuria - Schnell, Annika (Infection, 2024)
CRIS-Team Scopus Importer:2024-08-30